Exploring Ecological Crisis: A Study of Climate Change in Uzma Aslam Khan’s Thinner Than Skin (KEMANUSIAAN The Asian Journal of Humanities, 2024)
This article investigates Uzma Aslam Khan’s Thinner Than Skin (2012), through the critical lens of ecocritical perspectives. It shows engagement with ecological ideologies that have informed our understanding of climate change. Khan’s novel enlists the devastating consequences of environmental and ecosystem degeneration and their cumulative effects on humanity, and the non-human world. Indeed, ecological degradation has become a global issue, where desertification and deforestation are significant environmental concerns worldwide. This study probes the portrayal of the indigenous people of Pakistan’s Kaghan Valley, their land, history and culture by underscoring the hazards of growing capitalism and increasing urbanisation. Khan examines the issues of endangering biodiversity and laments the materialistic forces depleting the planet’s natural resources. By doing so, she exhorts practical consideration of possible defences against ecocide. This research demonstrates the issues of ecological crisis and its devastating impact on northern Pakistan’s natural environment and people.